Pengaruh Reward dan Insentif Terhadap Semangat Kerja Karyawan Pada PT. Basin Sejahtera Maritime Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2022)
ABSTRACTThis study aims to determine the effect of remuneration and motivational strength on employee guarantees at PT. Palembang Sea Flourishing Bowl. The strategy used in this study is a quantitative technique with the number of tests considered is 32 workers. The information checking strategy used in this exploration is a basic direct recurrence examination, direct recurrence examination, connection coefficient examination, assurance coefficient examination, t test and f test using the SPSS 23 for windows program. From the results of the t-test research shows that there is a reward (X1) with a critical value of 0.000 < 0.05, implying that there is a rather large impact of remuneration on the resolve of the representative. While the driving variable (X2) with a large value of 0.000